Analysis of Nonsteroidal Anti-inflammatory Drugs by using Microfluidic Techniques: A Review - Fanali, Chiara; D’Orazio, Giovanni; Gentili, Alessandra; Fanali, Salvatore (Current Pharmaceutical Analysis, 2021)
In this review paper, miniaturized techniques, including both electromigration and liquid chromatographic techniques, have been discussed considering their main features in the analytical field for the separation and analysis of Nonsteroidal Anti-inflammatory Drugs (NSAIDs). In Capillary Electrophoresis (CE) and nano-liquid chromatography (nano-LC), separation is performed in capillaries with Internal Diameter (I.D.) lower than 100 μm and therefore flow rates in the range 100-1000 nL/min are applied. Therefore, due to the low flow rate, high mass sensitivity can be obtained. Usually, conventional UV detectors are used on-line; however, these techniques can be coupled with Mass Spectrometry (MS). CE and nano-LC have also been applied to the separation of NSAIDs using silica stationary phases (SP) modified with C18 promoting interaction with analytes mainly based on hydrophobic interaction. Besides, the use of chiral SP was found to be effective for the chiral resolution of these compounds. In addition to silica phases, monolithic (both organic and inorganic) material has also been used. Although most of the presented studies aimed to demonstrate the usefulness of the considered microfluidic techniques, some applications to real samples have also been reported.
Keywords: capillary liquid chromatography